Treatable traits of small airway dysfunction in children with asthma and advances in small airway-targeted therapeutic research: a narrative review - Qin, Tao; Han, Wei; Yu, Yiyi; Yang, Jun (Translational Pediatrics; Vol 15, No 5 (May 31, 2026): Translational Pediatrics, 2026)
Small airway dysfunction (SAD) is highly prevalent in children with asthma and is closely associated with adverse outcomes, including poor disease control, frequent exacerbations, and impaired quality of life. However, conventional asthma management has traditionally focused on large-airway assessment, often leading to the oversight of SAD. The maturation of diagnostic techniques and the growing application of therapies with enhanced peripheral lung delivery have rendered targeted intervention increasingly feasible. Concurrently, the emerging “treatable traits” (TTs) paradigm provides a novel framework for personalized asthma management. This review aims to synthesize current evidence on small airway-targeted therapies and, building upon the TT framework, propose a stepwise clinical strategy to operationalize pediatric SAD as a distinct TT, in order to inform future research and guide the evolution of clinical practice.